Chronic low back pain is associated with impaired bed turning ability: Evaluation by a mobility detection system. (February 2022) - Lin, Chia-Huei; Lin, Chueh-Ho; Chen, Liang-Cheng; Wei, Shun-Hwa; Sung, Wen-Hsu; Lu, Liang-Hsuan; Chang, Shin-Tsu; Lin, Yi-Hui; Lee, Chun-Yi; Chiang, Shang-Lin
Abstract: Background: We aimed to assess and compare kinetics and kinematic variables of bed turning ability using a mobility detection system in patients with and without chronic low back pain and to observe the impacts of the disease on bed turning kinetics and kinematics. Methods: Thirty-five patients with chronic low back pain were enrolled and compared to healthy controls ( n = 34). Pain scores and disability level were assessed by Numeric Pain Rating Scale and the function questionnaires including Oswestry Disability Index and Roland Morris Disability Questionnaire. Bed turning ability was tested using the Mobile Detection System. Univariate and multivariate regression analysis were applied to compare the differences between groups. Findings: Patients with chronic low back pain had significantly lower turning over and back force/weight ratio ( p < 0.001) than those healthy controls. Turning over time was significantly longer in patients with Numeric Rating Scale score 3 than in those with Numeric Rating Scale score 2 ( p = 0.015). Turning over and back force were significantly higher in male patients and patients with higher BMI after adjusting BMI and sex, respectively (all p < 0.001). When turning back, chronic low back pain patients with Numeric Rating Scale scores of 3 had lower turning back force/weight ratio than those with Numeric Rating Scale scores of 2 ( p = 0.014). Male patients had higher turning back force/weight ratio after adjusting pain score ( p = 0.001). Interpretation: The novel Mobility Detection System can provide more objective assessments of bed turning kinetics and kinematics in patients with chronic low back pain. Highlights: Mobility Detection System provided objective assessments of bed turning kinematics. Pain was associated with turn over time and time to reach peak pressure. Sex and pain level were significantly associated with turning force/weight ratio.